Dumbbell-shaped hypoglossal schwannoma with cystic and hemorrhagic degeneration: A case report of a rare entity - Kaouthar Sfar; Fadwa Jaheddine; Kaoutar Maslouhi; Fatima Chait; Meriem Zhim; Najwa ECH-cherif El Kettani; Meriem Fikri; Mohamed Jiddane; Firdaous Touarsa (Radiology Case Reports)
Hypoglossal schwannoma (HS) is a rare, benign tumor arising from the myelin-producing Schwann cells of the twelfth cranial nerve. This tumor typically appears as solid mass, with cystic patterns being extremely rare. A. Kaye classified HS into 3 types based on their origin: type A, completely intracranial; type B, intracranial with extracranial extension via the hypoglossal canal, often referred to as ''dumbbell-shaped''; and type C, arising solely from the extracranial portion of the XII nerve. Tongue deviation and hypotrophy are the most common symptoms. MRI is the gold standard for accurately characterizing the lesion's features and assessing its relationship with the surrounding structures, while high-resolution CT scan of the skull base is valuable for surgical planning. The treatment of hypoglossal schwannoma (HS) is surgical excision. Advances in microsurgical techniques, radiosurgery and neurophysiological monitoring have significantly reduced mortality and morbidity. Here, we report a case of cystic dumbbell-shaped hypoglossal schwannoma in a 71-year-old woman, aiming to emphasize the clinical and radiological characteristics of this rare entity.